G-Quadruplex and protein binding by single-molecule FRET microscopy - Lee, Chun-Ying (Methods Mol Biol, 2019)
G-quadruplex (G4) is a non-canonical nucleic acid structure that arises from the stacking of planar G-tetrads, stabilized by monovalent cations. G4 forming sequences exist throughout the genome and G4 structures are shown to be involved in many processes including DNA replication and gene expression. The single molecule total internal reflection fluorescence (TIRF) microscopy has been employed to study G4 structure formation and protein binding interactions. Here, we describe methods by which we tested the folding and unfolding of G-quadruplexes structure and studied the dynamics of its interaction with POT1 protein. The methods presented here can be applied to study other putative G4 sequences and potential binding partners.